Islam dan Globalisasi: Sebuah Pandangan tentang Universalitas Islam - Khusnul Khotimah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Globalization is a historical fact that has significant influence on society’s life system. This condition has to facewith wise reaction. Islam as religion that have universal and global order, certainly have role on solving globalization problem.Its clear from its universality, Islam can have significant role to shape global community. Islamic universalism can be seenfrom several manifestations, e/g: cosmopolitan cultural teaching, science development, holistic social order and completevalues. From this, Islam universality is able to face economic, education, culture, technology and other problems